The Flora Malesiana Account of Grammitid Ferns (Polypodiaceae) : A Progress Report With an Illustrated Synoptic Key to Malesian Genera - Parris, Barbara S (Sibbaldia: the International Journal of Botanic Garden Horticulture, 2018)
Fourteen genera and approximately 373 species of grammitid ferns (formerly Grammitidaceae, now Polypodiaceae) occur in Malesia. The Flora Malesiana account of the group is 75% complete (280 species). The genera are illustrated and briefly described. Current studies involve working through species that have long been herbarium dumping grounds containing numerous undescribed species, such as Calymmodon cucullatus (Nees & Blume) C.Presl, Prosaptia contigua (G.Forst.) C.Presl, Radiogrammitis hirtella (Blume) Parris (as Grammitis hirtella) and Tomophyllum subfalcatum (Blume) Parris (as Ctenopteris subfalcata).